Oral Delivery of Macromolecular Drugs Barriers, Strategies and Future Trends - Bernkop-Schnürch, Andreas (Springer New York : Imprint: Springer, 2009)
Due to a rapid development in biotechnology more and more macromolecular drugs such as therapeutic peptides, oligosaccharides and nucleic acids are entering the pharmaceutical arena representing unprecedented challenges from the drug delivery point of view. One of the likely greatest challenges is their oral administration presenting a series of attractive advantages. Oral Delivery of Macromolecular Drugs addresses the most critical issues for a successful oral delivery of macromolecular drugs by a detailed characterisation of the 'enemy's strength' which is mainly based on the enzymatic barrier, the mucus gel barrier and the absorption barrier. Each of these barriers is described in detail in separate chapters by leading scientists in the field. The higher the knowledge about these barriers, the more potent oral macromolecular delivery systems can be generated. In the second part of this volume an overview on the likely most promising strategies to overcome these barriers is provided. Each of these strategies is described in detail in chapters being authored by worldwide academic and industrial experts. These strategies include the use of auxiliary agents such as polymeric and low molecular mass permeation enhancers, efflux pump inhibitors and enzyme inhibitors. Furthermore, these strategies are based on delivery systems such as liposomal formulations and micro- and nanoparticles. Oral Delivery of Macromolecular Drugs provides also an overview on special topics in oral macromolecular drug delivery such as oral immunization and gene delivery. Each of these chapters benefits from the results of various in vivo studies demonstrating the potential of discussed delivery systems. On the one hand macromolecular drugs can be produced more and more effectively making also low oral bioavailabilities in the range of 0.5 - 5% commercially interesting. On the other hand, oral macromolecular drug formulations are becoming more and more efficient. Taking these developments into consideration, the number of oral macromolecular delivery systems entering the market will increase considerably over the years. 'Invasive-to-oral-conversions' promise great rewards for those investing in this market. Oral Delivery of Macromolecular Drugs should encourage and motivate scientists in academia and industry to move in or intensively their activities in this challenging research field of great future. About the Editor Andreas Bernkop-Schnürch is the Dean of the Faculty of Chemistry and Pharmacy and Professor of Pharmaceutical Technology at the University of Innsbruck, Austria. His main interests focus on non-invasive drug delivery systems, multifunctional polymers such as thiomers, mucoadhesion and permeation enhancement. He is author of more than 200 original research and review articles and received the Research-Award of the City of Vienna (Vienna), EURAND-Award (Boston), Best of Biotech Award (Vienna), MBPW-Award (Munich), PHÖNIX Award (Mannheim), Houska-Award (Vienna) and Austrian-Nanoaward (Vienna). In addition, Andreas Bernkop-Schnürch is founder and owner of the following companies: ThioMatrix GmbH, Dr. K. Schnürch KG and Green River Polymers GmbH.